How do non-farm employment and agricultural mechanization impact on large-scale farming? A spatial panel data analysis from Jiangsu Province, China. (August 2021) - Li, Fang; Feng, Shuyi; Lu, Hualiang; Qu, Futian; D'Haese, Marijke
Abstract: In this paper, we search to link changes in non-farm employment and agricultural mechanization to the emergence of large-scale farming in China. Based on county-level data for the Jiangsu Province from 2002 to 2016, we use spatial panel data techniques to understand how the increase in large-scale farming in one county is explained by changes in employment and mechanization in the county itself as well as by changes in the neighboring counties. Our results confirm the presence of substantial spatial spillover effects. The level to which large-scale farming is present and expanding in one county is positively associated with local non-farm employment and agricultural mechanization levels. A local higher non-farm employment ratio also contributes to an increase in large-scale farms in neighboring counties. Hence, if a local government intends to support large-scale farming, it can bank on the creation of non-farm employment and support agricultural mechanization in the county it governs. Also economic and policy changes in the neighboring counties will induce land use transition when non-farm employment is created. Highlights: Large-scale farm expansion is spatially correlated among neighboring counties. Non-farm employment and agricultural mechanization promote local farm expansion. Economic and employment structures show obvious spillover effects in this process.